Genetic Distance and Cognitive Human Capital: A Cross-National Investigation - Oasis Kodila-Tedika; Simplice A. Asongu (African Governance and Development Institute (AGDI), 2015)
This paper explores the determinants of intelligence by focusing on the role played by barriers to the diffusion of competence and human capital. The results based on cross-sectional data from 167 countries consisting of 1996-2009 averages suggest that, genetic distance to global frontiers has a negative relationship with human capital. Countries that are genetically far from leading nations tend to have lower levels of human capital with the negative correlation from the USA frontier higher relative to the UK frontier. The sign is consistent with the relationship of genetic diversity and robust to the control of macroeconomic, geographical, institutional and influential variables. Policy implications are discussed.
Keywords: G15; O50; O16; F15; N7; 330; Intelligence; Human Capital; Genetic distance